WNT10A and isolated hypodontia - Kantaputra P. (2017)
WNT10A has been associated with various syndromes with ectodermal dysplasia from severe autosomal recessive SchÖpf-Schulz-Passarge syndrome to odonto-onycho-dermal dysplasia and autosomal dominant hypodontia. We report WNT10A mutations in an American family of which four members are affected with isolated hypodontia or microdontia. Here we demonstrate that in addition to MSX1, PAX9, AXIN2, and EDA, mutations in WNT10A can cause isolated hypodontia. © 2011 Wiley-Liss, Inc.